Gambaran Persepsi Risiko Penyebaran Covid-19 di Tempat Kerja Pada Pekerja Hulu Migas di Lapangan Hijau PT. P: Covid-19 Risk Perception at The Workplace on Oil & Gas Upstream Workers at Hijau Field PT. P - Wahyu Dwi Astuti; Dadan Erwandi (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2022)
Introduction: COVID-19 pandemic has impacted all types of industries, including oil & gas industry. In spite of that, workers of Hijau Field at PT. P still work offline. Despite company’s policies to prevent the spread of COVID-19 have been implemented, COVID-19 cases are still found in the workplace, means that the risk of spread of COVID-19 in the workplace is still present Objective: This study aimed to describe COVID-19 risk perception at workplace on oil and gas upstream workers at Hijau Field PT. P Methods: 50 questions were launched online to employees in Hijau Field PT. P (n=234) using 9 psychometric dimensions with cross-sectional study design. The data were analyzed with descriptive statistic Results: The dimensions’ average lies between 2.35-3.71 (scale 4), with the highest dimension being Risk Control with average 3.71. Fear dimension is perceived the lowest with the average 2.35. Overall risk perception average is 3.42 where 56% of workers have good risk perception. Risk perception of workers below 30 years old, above 40 years old, and higher education is better than workers that in the age between 30-40 years old and middle education. Conclusion: Perception of workers of Hijau Field PT. P towards the risk of spread of COVID-19 in the workplace is good. Workers are of the opinion that the risk is controlled adequately by the efforts implemented by company and individuals. However, workers still consider that the risk of spread of COVID-19 still considerable to be reduced. The company has to maintain the efforts of preventing spread of COVID-19. Communication in the risk of spread of COVID-19 should be focused on workers with the age range 30-40 years old and middle education